Transformation of Stilbene Glucosides From Reynoutria multiflora During Processing - Bai, Junqi; Chen, Wanting; Huang, Juan; Su, He; Zhang, Danchun; Xu, Wen; Zhang, Jing; Huang, Zhihai; Qiu, Xiaohui (Frontiers in Pharmacology, 2022)
The root of Reynoutria multiflora Thunb. Moldenke (RM, syn.: Polygonum multiflorum Thunb.) has been widely used in TCM clinical practice for centuries. The raw R. multiflora (RRM) should be processed before use, in order to reduce toxicity and increase efficiency. However, the content of trans-2, 3, 5, 4′-tetrahydroxystilbene-2-O-β-D-glucopyranoside (trans-THSG), which is considered to be the main medicinal ingredient, decreases in this process. In order to understand the changes of stilbene glycosides raw R. multiflora (RRM) and processed R. multiflora (PRM), a simple and effective method was developed by ultra high performance liquid chromatography tandem quadrupole/electrostatic field orbitrap high-resolution mass spectrometry (UHPLC-Q-Exactive plus orbitrap MS/MS). The content and quantity of stilbene glycosideshave undergone tremendous changes during the process. Seven parent nucleus of stilbene glycosides and 55 substituents, including 5-HMF and a series of derivatives, were identified in PM. 146 stilbene glycosides were detected in RRM, The number of detected compounds increased from 198 to 219 as the processing time increased from 4 to 32 h. Among the detected compounds, 102 stilbene glycosides may be potential new compounds. And the changing trend of the compounds can be summarized in 3 forms: gradually increased, gradually decreased, first increased and then decreased or decreased first. The content of trans-THSG was indeed decreased during processing, as it was converted into a series of derivatives through the esterification reaction with small molecular compounds. The clarification of secondary metabolite group can provide a basis for the follow-up study on the mechanism of pharmacodynamics and toxicity of PM, and for screening of relevant quality markers.